Urgensi Pemimpin Adil dan Berpengetahuan Luas: Perspektif Anies Baswedan - Siti Habibah khumalia; Masduki Asbari (Journal of Information Systems and Management (JISMA), 2023)
The study aims to find out how to be a fair and knowledgeable leader. This report uses a qualitative descriptive method by listening closely because the data source was obtained by listening to the oral narrative from the CXO Media YouTube channel entitled "Becoming a Fair and Knowledgeable Leader" presented by Anies Baswedan. The results of this study explain that becoming a leader is not an easy matter. Never mind carrying out daily activities as a leader. Finding a position called "leader" is also equally difficult. Leadership is an important element in a company, because without leadership from a leader, a company will experience setbacks. Many have noted that leadership can influence organizational performance. However, the challenge becomes greater when you are required to be a fair leader. This research begins with the emergence of a revolution to become a just leader through education and has the aim of making education in Indonesia better and more equitable to all corners of Indonesia, as well as sharing the values ​​that are instilled in living life and pursuing dreams.